Development of Ulva lactuca Nori-like Products with Heritage Flavors from Traditional Fermented Products from Riau - M. Haekal Tiftazani; Joko Santoso; Wahyu Ramadhan (Sarana Ilmu Indonesia (Salnesia), 2026)
The demand for nori in Indonesia continues to rise; however, the limited availability of local raw materials, such as Porphyra sp., necessitates the development of alternative products based on other types of seaweed. This study aimed to evaluate the effects of adding terasi and rusip to the formulation of nori-like products made from Ulva lactuca on sensory, physical, and chemical characteristics. A Completely Randomized Design (CRD) was employed, consisting of one factor with four levels and three replications. The treatments involved varying formulations of terasi:rusip ratios (1:4, 2:3, 3:2, and 4:1). The best formula was determined based on hedonic sensory evaluation by trained panelists. The selected formula was then subjected to proximate analysis and color profiling. The results revealed that the best formulation was the 3:2 terasi:rusip ratio, which achieved the highest hedonic score for overall acceptability (4.5, categorized as